G-749 Promotes Receptor Tyrosine Kinase TYRO3 Degradation and Induces Apoptosis in Both Colon Cancer Cell Lines and Xenograft Mouse Models - Kim, Hae Dong; Park, Eun Jung; Choi, Eun Kyoung; Song, Seuk Young; Hoe, Kwang-Lae; Kim, Dong-Uk (Frontiers in Pharmacology, 2021)
G-749 is an FLT3 kinase inhibitor that was originally developed as a treatment for acute myeloid leukemia. Some FLT3 kinase inhibitors are dual kinase inhibitors that inhibit the TAM (Tyro3, Axl, Mer) receptor tyrosine kinase family and are used to treat solid cancers such as non-small cell lung cancer (NSCLC) and triple-negative breast cancer (TNBC). AXL promotes metastasis, suppression of immune response, and drug resistance in NSCLC and TNBC. G-749, a potential TAM receptor tyrosine kinase inhibitor, and its derivative SKI-G-801, effectively inhibits the phosphorylation of AXL at nanomolar concentration (IC50 = 20 nM). This study aimed to investigate the anticancer effects of G-749 targeting the TAM receptor tyrosine kinase in colon cancer. Here, we demonstrate the potential of G-749 to effectively inhibit tumorigenesis by degrading TYRO3 via regulated intramembrane proteolysis both in vitro and in vivo. In addition, we demonstrated that G-749 inhibits the signaling pathway associated with cell proliferation in colon cancer cell lines HCT15 and SW620, as well as tumor xenograft mouse models. We propose G-749 as a new therapeutic agent for the treatment of colon cancer caused by abnormal TYRO3 expression or activity.